2021
DOI: 10.1007/s11249-021-01451-9
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Onset of Plasticity in Sliding Contacts Using Differential Computational Orientation Tomography

Abstract: Depending on the mechanical and thermal energy introduced to a dry sliding interface, the near-surface regions of the mated bodies may undergo plastic deformation. In this work, we use large-scale molecular dynamics simulations to generate “differential computational orientation tomographs” (dCOT) and thus highlight changes to the microstructure near tribological FCC alloy surfaces, allowing us to detect subtle differences in lattice orientation and small distances in grain boundary migration. The analysis app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 58 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The results showed that the friction force is related to the dislocation slip direction, and the effect of grain boundaries and grain size on tribological behaviors were revealed: the grain boundary structure showed a strengthening effect, which hindered propagation of stacking fault; as the grain size decreased, the material softened, resulting in a decrease in friction coefficient and increase of wear depth. Furthermore, in order to better capture [931] innovatively proposed the "differential computed orientation tomography" (dCOT) method, based on large-scale MD simulations (Fig. 77(a)).…”
Section: Fundamentals Of Solid Friction and Wearmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that the friction force is related to the dislocation slip direction, and the effect of grain boundaries and grain size on tribological behaviors were revealed: the grain boundary structure showed a strengthening effect, which hindered propagation of stacking fault; as the grain size decreased, the material softened, resulting in a decrease in friction coefficient and increase of wear depth. Furthermore, in order to better capture [931] innovatively proposed the "differential computed orientation tomography" (dCOT) method, based on large-scale MD simulations (Fig. 77(a)).…”
Section: Fundamentals Of Solid Friction and Wearmentioning
confidence: 99%
“…Fig 77. Mechanism of friction and wear at atomistic scale[931,934,935,937]. Reproduced with permission from Ref [931],.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The computational tomographs of the polycrystalline CuNi sample shown and discussed throughout this work are colored according to grain orientations as in electron backscatter diffraction (EBSD), using the inverse pole figure (IPF) coloring standard (see Ref. [51] for an in-depth discussion). Orientations were calculated using polyhedral template matching [52] as implemented in OVITO [53], and the EBSD-IPF style colors were produced using the MTEX toolbox [54,55] for Matlab.…”
Section: Simulation and Visualization Detailsmentioning
confidence: 99%